AN ANALYSIS OF JARGON FOUND IN AN ANALYSIS OF INFORMATION TECHNOLOGY (IT ) JARGON FOUND IN PC MEDIA MAGAZINE - RIYAWATI, ERNA (Jurnal Ilmiah Mahasiswa FIB, 2013)
Language is very important for everyone as the members of society inorder to interact with others. Society itself gives contribution in creating languagevariation since there are multilingual speakers in society. One of the languagevariations is jargon.  In this study, the writer is interested in analyzing informationtechnology jargon because in this globalization era, information technology hasdeveloped and given a great contribution toward society.   In this study, the writer uses PC Media magazine January 2013 edition asthe object of the study focusing on six articles chosen. The writer formulates threeproblems of the study as follows: (1) what are the information technology jargonsfound in PC Media magazine, (2) what are the types of word formation processesfound in information technology jargons in PC Media magazine? and (3) what isthe meaning of derived word of information technology jargons found in PCMedia magazine?. This study used textual analysis since the writer analyzed the texts fromsix articles in PC Media magazine January 2013 edition as the data. There are 33information technology jargons found. In addition, the types of word formationprocesses occurred are six derivation processes, seven multiple processes, twoacronym processes, five alphabetic abbreviation processes, three compoundingprocesses, six borrowing indirect processes, and four clipping processes. Besides,the writer also found out the meaning of each jargon based on co-text. For further researchers, the writer suggests them to use other jargons to beanalyzed to add the variation of the research. The writer also suggests the nextresearchers to conduct a field research about jargon in a certain community orcertain hobby in order to have the enrichment of the study. Keywords: Information Technology Jargon, Word Formation Processes, PC Media Magazine.